Sudden Transition In Anatomy Education: Assessing The Perception Of Anatomy Course Delivery Among Medical Students During COVID-19 Pandemic - Amira Raudhah Abdullah; Mohamed Hanief Khalid; Noor Azzizah Omar; Ku Mastura Ku Mohd Noor; Mohd Hairulhisyam Ngatiman (USIM Press, 2024)
ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences (Special Issue IHEC 03-2021) [August 2021]